Replicating nature’s design in steel structures to enhance structural performance under transverse load - Yap, Kian Lim (2021)
Many structural buildings are conceptualised and designed with a key emphasis on vertical imposed loadings and lesser on lateral loadings (other than wind loading consideration). However, in landslide-prone areas, strong coastal waves or earthquakeprone areas, engineers counteract these lateral forces of nature with new and innovative design structures like retaining walls, breakwaters and mechanical dampers. The problem often gets complicated when the effects of earthquake come into the equations, particularly in tall building structures. The solution to the problem lies in nature, where they are suited to surviving the harshest environment. The research aims to enhance the efficiency of steel structures under lateral loading by replicating the design found in nature (trees). Since there is no study on utilising nature's notch shape profile and integrating nature's design in civil engineering structures, three separate linear studies were conducted. The first study compares the traditional cantilever beam designs against the cantilever beam with the projection according to the Method of Tensile Triangles (MTT) across the various loading conditions and beam depths. The second study investigates the various cantilever beam geometries' load paths to understand better their behaviour and structural performance through the topology optimisation technique. The third study investigates the feasibility of introducing columns with the Method of Tensile Triangles (MTT) projection in the connections or joints in steel multistorey moment-resisting frame structures under earthquake loadings. The studies found that the MTT cantilever beams perform best when the projection considered is small. The load path obtained through the topology optimisation study shows better utilisation of the projection in smaller. MTT cantilevers beam projections. In addition, the multistorey achieves better lateral resistance by introducing a better connections/joints system in both analysis under the equivalent lateral force method and the response spectrum. Hence, utilising the MTT shape profile or replicating nature's shape profile in steel structures can lead to better structural design. Thus, the size and shape of a structure play a pivotal role in the performance of a structure. However, it should be noted that further in-depth studies are still required to validate the numerical model and to expand the research further into other civil engineering structures, e.g., gravity walls, water dams and counterfort.